Endothelial Differentiation G Protein‐Coupled Receptor 5 Plays an Important Role in Induction and Maintenance of Pluripotency. (7th February 2019) - Neganova, Irina; Cotts, Lewis; Banks, Peter; Gassner, Katja; Shukurov, Anvar; Armstrong, Lyle; Ladds, Graham; Lako, Majlinda
Abstract: Direct reprogramming of human somatic cells toward induced pluripotent stem cells holds great promise for regenerative medicine and basic biology. We used a high‐throughput small interfering RNA screening assay in the initiation phase of reprogramming for 784 genes belonging to kinase and phosphatase families and identified 68 repressors and 22 effectors. Six new candidates belonging to the family of the G protein‐coupled receptors (GPCRs) were identified, suggesting an important role for this key signaling pathway during somatic cell‐induced reprogramming. Downregulation of one of the key GPCR effectors, endothelial differentiation GPCR5 ( EDG5 ), impacted the maintenance of pluripotency, actin cytoskeleton organization, colony integrity, and focal adhesions in human embryonic stem cells, which were associated with the alteration in the RhoA‐ROCK‐Cofilin‐PAXILLIN‐actin signaling pathway. Similarly, downregulation of EDG5 during the initiation stage of somatic cell‐induced reprogramming resulted in alteration of cytoskeleton, loss of human‐induced pluripotent stem cell colony integrity, and a significant reduction in partially and fully reprogrammed cells as well as the number of alkaline phosphatase positive colonies at the end of the reprogramming process. Together, these data point to an important role of EDG5 in the maintenance and acquisition of pluripotency. Stem Cells 2019;37:318–331 Abstract : Summary of the main findings generated from this study.